KONDISI VEGETASI PADA GUNUNG WARINGIN DI AREAL KHDTK TAHURA SULTAN ADAM KALIMANTAN SELATAN - Matnasir Matnasir; Gusti Syeransyah Rudy; Setia Budi Peran (Jurnal Sylva Scienteae, 2020)
This waringin mountain area is also part of the university education forest of hull mangkurat (ULM), which education forest area was formerly pointed through the Governor's Decree Number / DA. 144 / PH / 1980 dated 31 of 1980 with an area of 2000 Ha. The objectives of this study were to analyze the vegetation conditions in the KHDTK area including the Importance Value Index (INP), the species diversity index and the evenness index of the species. This research is expected to provide information to related parties about the condition of vegetation in the area. The growth rate criteria used for the vegetation analysis are as follows: at the highest seeding level of 30-150 cm, followed by stakes of <150 cm, Diameter <10 cm, with pole diameter 10-20 cm and at tree level> 20 cm in diameter . Species diversity in this area is moderate because each growth rate in the location of this research get result with value <2 and <3. Evenness level of each type of growth is relatively the same.Keywords: Important value index; diversity index; evenness index